Lector Innova, transformando la educación con recursos digitales (2023)
The main objective of this project is to improve reading comprehension and promote the efficient use of educational resources throughout the country. To achieve this purpose, an exhaustive study was carried out, which included 4 interviews with teachers from both public and private schools, and the application of surveys to 41 teachers. The purpose of these interviews and surveys was to understand how teachers use educational resources in their classes, how often they use digital platforms to search for materials and how they evaluate them before applying them to their students.